Theory and Scholarly Inquiry Need Not be Scientific to be of Value - Martin, Jack (Canadian Journal of Counselling and Psychotherapy, 2007)
In this rejoinder, the central thesis of "Against Scientism in Psychological Counselling and Therapy" is clarified further.